LEGAL ASPECTS OF LAND FORMATION UNDER REAL ESTATE OBJECTS - Nesterenko, S.; Baystruk, O.; Kondratuk, I.; Khalikov, S. (Municipal economy of cities. Series: «Economy science», 2022)
A land plot is a part of the land that has clearly defined boundaries, a certain location, natural properties, physical parameters, it also describes the legal and economic status. The main properties of the land plot can be considered: boundaries, area, cadastral number and address, as well as legal properties, namely the rights and obligations of the land owner, restrictions and encumbrances, land easements. In addition to these characteristics, there are also so-called quality, they include: the cost of use or exchange. When a land plot is formed, it becomes an object of civil law, and it is for this purpose that it is formed. Nowadays, with the creation of the land market, it is necessary that every owner or user of land has the right to draw up documents that are necessary for the sale or lease of land, and this includes work on the formation of land, and it is work on drawing up a land management project in accordance with. Depending on the available materials from the previous works on this site, the composition and scope of work required for the formation of the site are determined. These characteristics are also related to the reform, or in other words, the reorganization of agricultural enterprises. Two other factors that affect the composition and scope of work are the number and location of real estate to be transferred. There are also many other factors of influence. The purpose of the article is to study the principles of development of land management projects, taking into account the scheme of application of tools for the organization and protection of land. The paper analyzes modern domestic and international approaches to the development of land management projects and the formation of land management documentation at different levels and for different applications. The technology and systematized stages of creating a land management project are determined. Factors influencing the location of the real estate object are analyzed. It is determined that all the presented factors must be taken into account at all stages of the construction, starting with its construction and ending with its operation. But taking into account each individual factor in the efficiency of use or profitability of the building, if it is commercial, is not enough to choose the right location of the property. The principles of formation of land management documentation for construction purposes are determined. The developed directions in research will give the chance to increase land use by application of modern technological schemes of development of land management projects taking into account current requirements of the legislation.